Keanekaragaman Jenis dan Kelangkaan Tumbuhan dengan Status Terancam di Taman Hutan Raya Lapak Jaru, Kabupaten Gunung Mas : Species Diversity and Rarity of Threatened Plants in Lapak Jaru Forest Park, Gunung Mas Regency - Setiarno Setiarno; Nisfiatul Hidayat; Ajun Junaedi; Herwin Joni; Reky Reky (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
This study aims to analyze the composition, describe the species diversity, and assess the rarity of plant species with threatened status at the Lapak Jaru Forest Park (Tahura), Gunung Mas Regency. Plant data were collected using the quadrat method, with plot units placed along observation trails in three management blocks (Utilization, Plant Collection, and Protection). This study successfully identified 59 plant species belonging to 34 genera and 23 families. Shorea sp. and Shorea seminis consistently dominated strongly across all study blocks and growth phases. Plant density values simultaneously decreased with increasing growth stages. There was no indication of species dominance concentration (C = 0.06–0.20), the H’ value is classified as moderate (1 < H’ ≤ 3.22), reflecting sufficient species diversity and relative abundance; the richness index ranges from 2.49 to 4.83, generally classified as moderate (R = 3.5–5.0); and the evenness index is nearly even (E = 0.76–0.95). Two species are classified as threatened: Ramin (Gonystylus bancanus) in the CR (Critically Endangered) category and Ulin (Eusideroxylon zwageri) in the VU (Vulnerable) category.